Philo of Alexandria, On cultivation - Philo, of Alexandria. (Philo of Alexandria Commentary Series, 2013)
The Jewish exegete and philosopher Philo of Alexandria has long been famous for his allegorical treatises on the Greek Bible. The present volume contains the first translation and commentary in English on his treatise De agricultura ( On cultivation ), which gives an elaborate allegorical interpretation of Genesis 9:20. Noah's role as a cultivator is analysed in terms of the ethical and spiritual quest of the soul making progress towards its goal. The translation renders Philo's baroque Greek into readable modern English. The commentary pays particular attention to the treatise's structure, its biblical basis and its exegetical and philosophical contents. The volume will be valuable for the insights it gives into an unusual but highly influential method of biblical interpretation.